Application of the cognitive load theory in prelicensure nursing education: a quantitative measurement focusing on instructional design. - Smith, Nicole E.; Barbé, Tammy; Randolph, Justus (International Journal of Nursing Education Scholarship, 2022)
The objective of this study was to examine differences in principles from the cognitive load theory (CLT) combined with active learning strategies. To examine these differences, simple to complex activities were imbedded into two active learning instructional strategies: cooperative learning (CPL) and problem-based learning (PBL) and evaluated for its impact on mental effort for learning and intrinsic cognitive load. A two-within repeated-measures design was used in a nursing fundamentals classroom. The simple and complex activities were grounded in recommendations from the CLT and validated by nurse experts. The instructional strategies of CPL and PBL were chosen based on recommendations from the literature. Results revealed no statistically significant differences. A small interaction showed a decrease in mental effort and intrinsic load when problem-based learning was used. Progressing learning activities from simple to complex, informed by the CLT, offers an approach to designing instruction in nursing classrooms when using active learning strategies.